Pengaruh Corporate Social Responsibility (Csr), Profitabilitas, dan Leverage Terhadap Kinerja Keuangan Perusahaan (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2019) - Rivona Yuniska Qilmi (Neraca : Jurnal Akuntansi Terapan, 2021)
This research aims to determine the effect of Corporate Social Responsibility (CSR), profitability, leverage on financial performance in mining companies listed on the IDX in 2016-2019. The data used in this research is quantitative data where the data is obtained from annual reports. The sampling method used in this research is purposive sampling method. Based on the sampling method, obtained a different sample each year and obtained as many as 125 data. The data analysis method used in this study is multiple linear regression analysis using SPSS version 21 software. Partially, Corporate Social Responsibility has no significant effect on the company's financial performance, while Profitability and Leverage have a significant positive effect on the company's financial performance. Simultaneously, Corporate Social Responsibility, Profitability, and Leverage together have a significant effect on the company's financial performance.